Pemberian pesan Dietary Approaches to Stop Hypertensions-like diet melalui whatsApp untuk memperbaiki kepatuhan diet dan tekanan darah pasien hipertensi - Arum Wulandari; Weni Kurdanti; Idi Setiyobroto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Giving Dietary Approaches to Stop Hypertension-like diet messages via WhatsApp to improve dietary compliance and blood pressure in hypertensive patientsBackground: Dietary Approaches to Stop Hypertension-like diet (DASH-like diet) is a non-pharmacological management of hypertension. The delivery of health information is currently being developed through social media such as WhatsApp.Objective: To determine the effect of giving DASH-like diet messages via WhatsApp on the compliance of DASH-like diet and blood pressure in hypertensive patients. Methods: This study used a quasi-experiment by one group pretest-posttest design approach. The location was taken at Kasihan II Health Center Community with 26 hypertensive patients for the sample. Univariate analysis using the Shapiro-Wilk test. Wilcoxon test for analysis of the compliance scores of DASH-like diet and diastolic blood pressure analysis. Systolic blood pressure analysis used paired sample t-test with a 95% confidence level. Results: There was a significant difference in DASH-like diet compliance score (p=0,001) and systolic blood pressure (p=0,021) between before and after the intervention. In contrast, there was no significant difference in diastolic blood pressure before and after the intervention (p=0.110). Conclusion: Giving a DASH-like diet message can significantly increase compliance with a DASH-like diet and systolic blood pressure and reduce diastolic blood pressure, although not significantly.